THE INITIAL IDENTIFICATION OF RAFFLESIA IN THE ANAMBAS ISLANDS, RIAU ISLANDS PROVINCE, AND THE CALL FOR PROTECTION - Yoppie Christian; Alin Rahmah Yuliani; Andy Afandy; Budi Prabowo; Ari Gunawan; Desmiwati; Nuke Susanti (Indonesian Journal of Forestry Research, 2026)
Rafflesia sp., which was found in the Bukit Batu Tabir Production Forest area on Siantan Island, Anambas Islands Regency, Riau Island Province, became the starting point for further research. However, its existence in relatively unmanaged Production Forests carries a risk of damage from human behavior because the presence of Rafflesia sp. has been known to the public since 2014. Based on the Direction Letter from the Riau Islands Provincial Environment and Forestry Office No. 13/070/1268.1/DLHK-04/2023 Medco E&P Natuna Ltd. together with the Center for Coastal and Marine Resources Studies IPB University, and the Production Forest Administration (KPHP) Unit VI of the Anambas Islands conducted an initial survey to identify species and surrounding habitats and build discussions with multi-stakeholders at the local level for the protection of Rafflesia sp. and their habitat. The research used morphological and observation methods, secondary data references, and discussions with related parties and Tarempa Selatan Village’s government. The research indicated that the species in Bukit Batu Tabir, Siantan Island, was the Rafflesia haseltii species. This is a new finding of R. haseltii in the archipelagic landscape. Previous findings of R. haseltii were found on the mainland of Sumatra and Kalimantan Island. The interviews and discussions with the parties indicated that there are initiatives to protect Rafflesia sp. and its area in a collaborative scheme using the Social Forestry Village Forest mechanism. However, further studies are still required to determine the precise species based on microstructure studies and to strengthen the model of protection and management.